Suitability Assessment of Two Different Culture Systems for the Rearing of Clarias gariepinus Fingerlings - Ekaete Patrick Anwa-Udondiah; I. O. Soboyejo; O. A. Okunade; B. M. Lawal; A. S. Aboluwodi; O. V. Oyeniyi (Department of Aquaculture, 2023)
This paper presents an experiment in which two different fish culture system types were evaluated for the short-term commercial culture of fingerlings of Clarias gariepinus maintained at half the recommended stocking rate; 82.5/m3 in 2 m3 water volume in indoor blue fiber-glass tanks (IFT) and outdoor black plastic tanks (OPT). The research objectives were to assess the suitability and commercial viability of the tanks. Initial mean body weight of graded fingerlings of C. gariepinus for IFT and OPT were 11.32±2.25 g and 10.92±2.44 g (mean±standard deviation) respectively. The study lasted for eight weeks with the fish attaining post-juvenile sizes of 174.95±74.30 g and 178.84±52.04 g (mean±standard deviation) in the IFT and OPT respectively which were not significantly different at p > 0.05. Survival at termination was 81.21±0.0% and 81.21±2.5% for IFT and OPT respectively. As fish attained larger sizes of 100 g and above between weeks 6 and 8, skin lesions and frayed fins were observed in comparatively more of the indoor reared fish than the outdoor reared fish. It may be concluded that the systems are not vastly different in terms of resultant survival and growth performance of the African catfish, however, the culture duration may be halved when maintaining the reported stocking rate in order to prevent distress as a fallout of aggression as they increase in size.